Relief Yeh Pulu Sebagai Warisan Sejarah Bali Kuno: Representasi Filsafat Tri Hita Karanay - Kristina, Ni Luh Wika; Aman; Yuliantri, Rhoma Aria Dwi (PURBAWIDYA, 2025)
This study aims to analyze the relationship of the Yeh Pulu Relief as one of the cultural heritage in the 14th century in Bali with the concept of Tri Hita Karana, as well as examine its relevance in the context of modern life. The Yeh Pulu relief not only holds aesthetic and historical value, but also represents the harmony of the relationship between humans and God (Parahyangan), fellow humans (Pawongan), and the environment (Palemahan). The approach used in this study is qualitative, through literature study methods, interviews and field observations. In analyzing the Relief, Yeh Pulu utilizes the theory of symbolic interaction used to reveal the meaning that social relations formed in ancient traditional Balinese society, while the theory of semiotics helps in interpreting the visual signs and symbols engraved on the Yeh Pulu Relief. The results of this study show that the various contained in the Yeh Pulu Relief represent the values of the Tri Hita Karana, such as agricultural activities that reflect harmony with nature (Palemahan), social interaction in the scene of community life (Pawongan), and the existence of spiritual figures or figures that symbolize the relationship with God (Parahyangan). This finding confirms that the Yeh Pulu Relief not only reflects the Balinese life philosophy of the time but the values in the Yeh Pulu Relief can be an inspiration in building a balanced and sustainable modern life.